2022
DOI: 10.1155/2022/1619651
|View full text |Cite
|
Sign up to set email alerts
|

MDL-800, the SIRT6 Activator, Suppresses Inflammation via the NF-κB Pathway and Promotes Angiogenesis to Accelerate Cutaneous Wound Healing in Mice

Abstract: Sirtuin 6 (SIRT6) is an NAD+-dependent deacetylase belonging to the sirtuin family. It has been shown to participate in wound healing and some inflammation-related disorders. However, the effect of MDL-800, a highly efficient and selective SIRT6 activator, on wound healing and inflammation has not been reported. Therefore, this study investigated whether MDL-800 confers anti-inflammatory effects and promotes wound healing and uncovered the molecular mechanisms involved. This was achieved using mouse models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“… 55 One recent study verified that SIRT6 suppressed inflammatory responses and downregulated the expression of inflammatory factors interleukin (IL)-6 and TNF-α via the NF-κB pathway. 56 For example, both SIRT1 and SIRT6 inhibited TNF-α-induced inflammation of vascular adventitial fibroblasts through reactive oxygen species (ROS) and the protein kinase B (Akt) signaling pathway. 57 SIRT1 exerted anti-inflammatory effects against IL-1β-mediated pro-inflammatory stress through the Toll-like receptor 2 (TLR2)/SIRT1/NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“… 55 One recent study verified that SIRT6 suppressed inflammatory responses and downregulated the expression of inflammatory factors interleukin (IL)-6 and TNF-α via the NF-κB pathway. 56 For example, both SIRT1 and SIRT6 inhibited TNF-α-induced inflammation of vascular adventitial fibroblasts through reactive oxygen species (ROS) and the protein kinase B (Akt) signaling pathway. 57 SIRT1 exerted anti-inflammatory effects against IL-1β-mediated pro-inflammatory stress through the Toll-like receptor 2 (TLR2)/SIRT1/NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided insights into NF-κb/IκB signaling, which exerts significant influences on the system-wide oxidative stress response, macrophage polarization and inflammation [ 41 , 42 ]. It was reported that the NF-κB/IκB signaling pathway played an important role in wound healing [ 43 ]. Suppression of the NF-κB/p65 pathway in fibroblasts promoted skin wound repair [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 It operates through various signaling pathways, notably the NF-κB pathway. 26 The activation of this pathway by IL-6 leads to the suppression of pro-inflammatory cytokines such as TNF-α, thereby exerting anti-inflammatory effects that are beneficial for healing. This dual role of IL-6, as both a promoter of initial inflammatory response and a mediator of subsequent healing processes, underscores its complex and critical function in wound healing dynamics.…”
Section: Cytokines Involved In Wound Healingmentioning
confidence: 99%
“…This dual role of IL-6, as both a promoter of initial inflammatory response and a mediator of subsequent healing processes, underscores its complex and critical function in wound healing dynamics. 26 Interleukin-17 (IL-17). IL-17 plays a significant role in skin tissue by stimulating immunological responses and inflammation.…”
Section: Cytokines Involved In Wound Healingmentioning
confidence: 99%